2002
DOI: 10.3904/kjim.2002.17.4.211
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vascular Endothelial Growth Factor VEGFand p53 Status for Angiogenesis in Gastric Cancer

Abstract: Background :Angiogenesis is of crucial importance for tumor growth and development of metastases. Vascular endothelial growth factor (VEGF) has a potent angiogenic activity and mutations of the p53 gene has been thought to upregulate VEGF. The purpose of our study was to evaluate the prognostic significance of these tumor biomarkers for angiogenesis relative to the information derived from established clinicopathological parameters in gastric cancer.Methods :In this study, we conducted an immunohistochemicai i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
6
16
0
9
Order By: Relevance
“…Studies on the association between MVD and prognosis in gastric cancer have produced inconsistent results; some have found that MVD is a predictor of poor prognosis, whereas others have found that MVD predicts good prognosis (11, 13, 15, 29 -35). In the present study, overall survival was significantly lower in patients with a high MVD than in patients with a low MVD, which is consistent with several previous reports (11,14,32,33,36,37). However, multivariate analysis revealed that MVD was not an independent prognostic indicator, whereas Stat3 was.…”
Section: Discussionsupporting
confidence: 82%
“…Studies on the association between MVD and prognosis in gastric cancer have produced inconsistent results; some have found that MVD is a predictor of poor prognosis, whereas others have found that MVD predicts good prognosis (11, 13, 15, 29 -35). In the present study, overall survival was significantly lower in patients with a high MVD than in patients with a low MVD, which is consistent with several previous reports (11,14,32,33,36,37). However, multivariate analysis revealed that MVD was not an independent prognostic indicator, whereas Stat3 was.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, our results suggest that p53 and VEGF regulate tumour angiogenesis in patients with gastric cancer, but they do not support the fact that p53 stimulates the appearance of new vasculature by enhancing the expression of VEGF. Reviewing the literature, we found three clinical studies with similar findings as ours, confirming that the expression of p53 does not correlate with VEGF expression in gastric cancer patients Giatromanolaki et al, 2000;Joo et al, 2002).…”
Section: Discussionsupporting
confidence: 70%
“…VEGF production has been found to be regulated by growth factors, cytokines, oncogenes, anti-oncogenes and other extra cellular molecules, such as hypoxia, p53 gene, TGF-α [28][29][30][31][32] . But few investigations have been concerned with relationship between VEGF and iNOS.…”
Section: Correlation Between Vegf and Inos In Gastric Cancermentioning
confidence: 99%